UJI EFEK DIURETIK INFUS BIJI JAGUNG (Zea Mays L), RAMBUT JAGUNG DAN KOMBINASI ANTARA KEDUANYA PADA KELINCI JANTAN (Oryctolagus Cuniculus) BERDASARKAN PARAMETER FREKUENSI URINASI DAN VOLUME URIN - Hendra Herman; Rizqi Nur Azizah; Chikita Inaku (Fakultas Farmasi UMI, 2012)
Has been done research Diuretic effect test of seed corn infusem, hair Corn infuse and combination of both in order to determining diuretic effect with frequency urination and volume urine parameters. This research use trial animals as many as 15 male rabbits, divided into 5 groups and each group consisted of three tails, group I is control that given colloidal solution of Na.CMC 1 %, group II infuse corn (Zea mays L) 23 33 mg group III has Qvien seed corn infuse (Zee mays L ) 466,664 gr, group IV has Given combination of hair and sedd corn infuse and group V is comparator that given suspension of furosemid Treatment done orally with a dose of 20 / 2,5 kg for further observation and measurement frequency done diuretic and urine volume intervals of 1 hour for 5 hours after treatment The result showed that infuse of seed corn, hair corn and combination of both can increase the frequency of urination, and just infuse of seed corn and hair corn increase the volume win of rabbits This is supported by statistical analysis methods CRD (Completely Randomized Design) For the frequency of urination infuse of seed corn, hair corn, and combination of both did not significantly different with furecemid while for the volume urine hair corn infuse and seed corn infuse are significantly different with Na CMC and not significantly different with furosemidKey words: Diuretic, seed and hair corn Infuse